2012
DOI: 10.3748/wjg.v18.i19.2377
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sequential and 7-, 10-, 14-d triple therapy forHelicobacter pyloriinfection

Abstract: There are no significant differences between 10-d sequential eradication therapy for H. pylori and any duration of standard triple treatment in Korean patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 35 publications
0
53
0
1
Order By: Relevance
“…Full-text of the seven remaining articles was reviewed and one article was removed. The remaining six RCTs were eligible for meta-analysis 10-15…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-text of the seven remaining articles was reviewed and one article was removed. The remaining six RCTs were eligible for meta-analysis 10-15…”
Section: Resultsmentioning
confidence: 99%
“…We considered RCTs with a score of 3 or greater to be high quality. In one RCT, participants of the TT group were randomly assigned to three groups according to treatment duration: 7-, 10-, and 14-day regimens 10. Since the object of our review was to compare ST with TT, we combined all the TT therapy arms into a single TT group.…”
Section: Methodsmentioning
confidence: 99%
“…A randomized-controlled study published in 2007 indicated no difference of eradication rate between 7 days-regimen and 14 days-regimen (intention-to-treat [ITT] analysis: 71.2% and 75.5%, respectively) [25]. Another study published in 2012 also demonstrated no significant difference among 7 days-, 10-days, and 14-days regimens (ITT analysis: 70.4%, 74.7%, and 80.0% respectively, P=0.244) [26]. Although the current guideline still recommends the conventional triple therapy for 7 to 14 days as first-line H. pylori eradication therapy, clinicians should be cautious for treating H. pylori infection with the conventional triple therapy.…”
Section: Conventional Triple Therapymentioning
confidence: 93%
“…In 2011, sequential therapy for 10 days was shown to be superior to conventional triple therapy for 14 days (ITT analysis: 85.9% vs. 75.0%, P=0.006) [37]. In 2012, three studies were published, and two of them demonstrated superior efficacy of sequential therapy compared to conventional triple therapy for 7 days (ITT analysis: 62.2% vs. 77.8%, P=0.002; 63.0% vs. 79.3%, P=0.005) [38,39], while the remaining one did not show statistical difference of eradication rate among sequential therapy and various triple therapy regimens (ITT analysis: sequential therapy vs. 7 days-triple therapy vs. 10 days-triple therapy vs. 14 days-triple therapy, 75.6% vs. 70.4% vs. 74.7% vs. 80.0%, P=0.416) [26]. In 2016, a nationwide multi-center randomizedcontrolled trial showed that sequential therapy had better eradication rate than conventional triple therapy as a first-line treatment of H. pylori infection (ITT analysis: 82.4% vs. 70.8%, P=0.001) [40].…”
Section: Sequential Therapymentioning
confidence: 99%
“…However, as the failure rate of the 7-day triple therapy has increased progressively, sequential or concomitant therapy has come to be used (3,5). Unfortunately, the 7-day triple therapy is still regarded as the standard primary therapy in South Korea because there is no proven alternative regimen that can provide more efficient and safer eradication (6,7). The unsatisfactory response of alternative eradication regimens was mainly caused by antimicrobial resistance and was particularly due to clarithromycin resistance (5,8).…”
mentioning
confidence: 99%